As razões trigonométricas no triângulo retângulo e as rampas de acesso - Arantes, Priscila Paschoali Crivelenti Vilela (2013)
This work is a math lesson on the triangle trigonometric ratios, using analysis of access ramps for people with special needs mobility. The mathematical content designed to be taught in grade 8/9 years of elementary school, according to the teaching experience of a teacher who devised and applied that lesson, there used to be presented to students in a way that justified the understanding it. This observation led to the idealization of a classroom where students participate in an active construction of knowledge and context. Students were led to reflect on the inclusion of people with special needs in today's society and to examine the access ramps of the school they attend, comparing your measurements with the Brazilian standard ABNT governing accessibility in buildings and structures. From the analysis of these ramps have been developing activities in order to build the concept of sine, cosine and tangent in rightangled triangle and attach to these concepts, meanings. They are extremely interested throughout the development of the work, which was completed fulfilling the objectives